Curcubinoyl flavonoids from wild ginseng adventitious root cultures - Qing Liu (Nature Portfolio, 2021)
Abstract Wild ginseng (Panax ginseng) adventitious root cultures were prepared by elicitation using methyl jasmonate and investigated further to find new secondary metabolites. Chromatographic fractionation of wild ginseng adventitious root cultures led to the isolation of eleven compounds. The chemical structures of isolated compounds were identified as four known flavanone derivatives (1–4), one new curcubinoyl derivative, jasmogin A (5) and six new curcubinoyl-flavanone conjugates, jasmoflagins A-F (6–11) by extensive spectroscopic analysis. Newly isolated curcubinoyl derivatives showed inhibitory activity against lipopolysaccharide-stimulated nitric oxide production in RAW 264.7 macrophages. Therefore, our present study suggested that elicitor stimulated plant cell cultures might contribute to the production of new metabolites.